SIRT5 rs12216101 T>G variant is associated with oxidative stress and mitochondrial dysfunction in patients with non-alcoholic fatty liver disease. (March 2023) - Salomone, F.; Pipitone, R.M.; Longo, M.; Malvestiti, F.; Casirati, E.; Distefano, A.; Amorini, M.; Volti, G. Li; Ciociola, E.; Lazzarino, G.; Craxì, A.; Fracanzani, A.L.; et al.
Abstract : Introduction: Sirtuin 5 (SIRT5) is a NAD+-dependent deacylase that modulates mitochondrial processes and the antioxidant defense through post-translational modifications of target proteins. Aim: In this study, we aimed to evaluate the impact of SIRT5 rs12216101 T>G on disease severity in patients with non-alcoholic fatty liver disease (NAFLD). We also aimed to assess if SIRT5 rs12216101 T>G genotype may influence mitochondrial function and oxidative stress in NAFLD. Materials and Methods: The rs12216101 was genotyped in 2606 consecutive European patients with biopsy-proven NAFLD. Genotyping of SIRT5 rs12216101 variants was performed by TaqMan assays. Parameters of mitochondrial function and oxidative stress were evaluated in a sub-cohort of 28 patients. Effects of SIRT5 pharmacological inhibition was evaluated in HepG2 cells exposed to free fatty acids (FFA) and mitochondrial energetics was investigated by HPLC. Results: At multivariate logistic regression analysis adjusted for gender, age>50 years, diabetes, and PNPLA3 rs738409 status, SIRT5 rs12216101 T>G variant was associated with presence of F2-F4 fibrosis (OR 1.18, 95% C.I. 1.00-1.37). Parameters of oxidative stress including reactive oxygen species, reactive nitrogen species and malondialdehyde were higher in patients carrying the T>G allele, whereas liver ATP was significantly lower. Exposure of HepG2 to FFA impaired mitochondrial energetics and determined oxidative stress. Administration of a pharmacological SIRT5 inhibitor to HepG2 treated with FFA preserved mitochondrial function as evidenced by restored ATP/ADP, NAD+/NADH and NADP+/NADPH ratios. Conclusions: The SIRT5 rs12216101 T>G variant is associated with liver damage, impaired mitochondrial function and oxidative stress in patients with NAFLD.